Nursing Strategies for Supporting Substance Abuse Recovery: A Comprehensive Review of Best Practices and Their Impact on Patient Outcomes - Alsharari, Turki Madallah Awadh; Alsharari, Saleh Sulaiman Salem; Mubark, Nawal Ali; Alkhaldi , Hammad Abduljabbar; Aldokhel , Tariq Abdulaziz M; Alhabas, Faljaa Ibrahim; Al-Shahdani, Abdullah Saeed Abdullah; Aldhafeeri , Huda Khalid Ajmi; Al Marzooq, Hassan Abdulhameed Salman (Journal of Ecohumanism, 2024)
Substance abuse and addiction present significant challenges to healthcare systems, necessitating effective nursing strategies that facilitate recovery. Recovery-oriented care emphasizes a holistic approach that encompasses individual wellness, autonomy, and community integration.This review employs a scoping review methodology to evaluate current literature on nursing strategies for supporting individuals with substance use disorders. A comprehensive search was conducted across multiple databases, including PubMed, MEDLINE, and Scopus, focusing on studies from 2010 to 2023 that address recovery-supportive interventions in nursing practice.The findings highlight several key nursing strategies that are essential for promoting recovery, including the integration of peer support, individualized care plans, and the establishment of trusting relationships between nurses and patients. The literature indicates that recovery-oriented practices lead to improved patient outcomes, including reduced substance use, enhanced quality of life, and better engagement in treatment programs. However, barriers such as stigma, lack of training, and systemic challenges persist.Effective nursing strategies that prioritize recovery-oriented care are critical for improving outcomes for individuals with substance use disorders. By fostering collaboration, empowering patients, and utilizing peer support, nurses can significantly enhance the recovery process. Continued research and training in recovery-oriented practices are essential to bridge the gap between current guidelines and actual nursing practices.